Poly‐γ‐Glutamic Acid Microgel‐Encapsulated Probiotics with Gastric Acid Resistance and Smart Inflammatory Factor Targeted Delivery Performance to Ameliorate Colitis. (23rd March 2022) - Wang, Rui; Guo, Kun; zhang, Weijie; He, Yineng; Yang, Kai; Chen, Qian; Yang, Liang; Di, Zhengao; Qiu, Jiangkai; Lei, Peng; Gu, Yian; Luo, Zhengshan; et al.
Abstract: Hydrogel microspheres with probiotic‐loaded therapy have been considered an effective and safe strategy for treating inflammatory bowel disease (IBD). However, the low survival rate under harsh stomach conditions and inflam‐matory cytokine target release efficiency remains a major challenge for their application. Herein, a novel NO‐responsive poly‐γ‐glutamic acid (γ‐PGA) hydrogel microcapsule (NRPM) strategy based on a droplet microfluidic technology platform is proposed. Accordingly, highly uniform microspheres with high cell densities (6.0 × 10 8 cells mL −1 ) and a wide range of diameters (100–600 μm) are produced, which are critical for realizing accurate down‐stream evaluation and applications. Owing to the cytoprotective effects of the NRPM, the decorated probiotics showed high viability in the simulated gastric (89.67%) and intestinal (93.67%) fluid environments, while the data are 0% and 61.60% for free cells, respectively. Moreover, both in vitro and in vivo studies demonstrate that microspheres can respond to nitric oxide (NO) stimuli and rapidly release probiotics to maintain the intestinal mechanical barrier and regulate the balance of intestinal flora. Consequently, NRPM significantly increases the treatment efficacy against dextran sulfate sodium‐induced colitis in a mouse model. The results demonstrate that NRPM is a promising approach for improving the efficacy of orally administered probiotics in patients with colonic IBD. Abstract : A novel approach is introduced for the production of NO‐responsive poly‐γ‐glutamic acid hydrogel microcapsule (NRPM) with probiotics encapsulation. Based on the droplet microfluidic technology platform, highly uniform microspheres (300 µm) with high cell densities (6.0 × 10 8 cells mL −1 ) are produced. Significantly, it exhibits excellent gastric acid resistance and smart inflammatory factor targeted delivery performance to ameliorate colitis.